Telecontrol equipment and systems. Telecontrol protocols compatible with ISO standards and ITU-T recommendations. Functional profile for providing the connection-oriented transport service in end system connected via permanent access to a packet switched data network Part 6-601, (15th September 1995) - British Standards Institution,
No abstract available